Intervenção psicopedagógica com criança disléxica: um estudo de caso na Escola de Educação Básica da Universidade Federal da Paraíba - Silva, Fabiana Maria Soares da (2016)
Learning difficulties have been widely discussed in Human Sciences studies and researches, since it is a fact that deserves attention and theoretical deepening because it involves psychosocial, biological and intellectual factors. From this point, comes out the need to identify the discrepancy between a difficulty and a learning disorder, giving attention to dyslexia. Dyslexia impairs the one’s learning, since it is a hereditary disorder that interferes with the decoding in the act of reading, writing, in Mathematics performance and in space sense. The aim of this research was to understand the role of psychopedagogical and multidisciplinary interventions as mediation for the development and learning of a dyslexic child in the School of Basic Education of the Federal University of Paraíba, as well as to know the learning process and sociability of the dyslexic child; contributing to the reading and writing of the dyslexic child and develop psychopedagogical methods which help the development and learning of children with dyslexia.